Description of Socialization Ability in Isolation Patients in Psychiatric Hospital Province, West Java, Indonesia - Andria Pragholapati; Naricho Yudha Wiratama; Rizki Muliani (Journal of Health Science Community, 2022)
The high number of mental health disorders is a major health problem when compared with other health problems in the community. Social isolation is where individuals or groups experience or feel the need to increase involvement with others but don’t want to make a contract. The purpose of this study was to determine the description of the ability of socialization in patients with social isolation at the West Java Provincial Mental Hospital. The research method used is quantitative with a cross-sectional design, a sample of 22 respondents were taken with a purposive sampling technique. Research instruments with a questionnaire or questionnaires. With univariate analysis using the Shapiro-Wilk test. The results of the study based on the Shapiro-Wilk test between the socialization ability obtained p-value of 0.709, which means greater than 0.05 so it can be concluded the description of the ability of socialization in patients with social isolation at the West Java Provincial Mental Hospital is good, so it is recommended for patients of social isolation should always be included in all activities whether TAK, morning exercise, or activities in the rehab room so that they can quickly be able to socialize again like normal daily activities